District Health System now more than ever: A lesson From The Past- Sudan - Elsheikh Elsiddig, Taha Ahmed Elmukashfi (Gezira Journal of Health Sciences, 2017)
Efforts to increase access to primary health care are ongoing in Sudan. Many health facilities were established and many health personnel were trained. As time passes, there is great concern about the sustainability as well as the effectiveness of these services due to lack of efficient local health system.  With the establishment of federal system, Sudan was divided into states and localities with division of responsibilities between different levels. Health, in most of the cases, is the responsibility of states and localities. Tremendous efforts are going on to develop the capacity of states with few attempts to develop the local health system. This short communication aims to through light on the experience of health area policy in Sudan. The concentration will be on the experience of Umshanig health area (1982 -1986), East Gezira which is the first in Sudan. Though the time was change, still lessons can be obtained from this experience.